Assessment of Nutrition-Sensitive Value Chains in the Feed the Future Zone of Influence in Tajikistan - International Food Policy Research Institute (International Food Policy Research Institute, 2023)
This dataset contains household and farm survey data collected in 2018 in 12 districts (USAID's Zone of Influence) in southwest Khatlon, Tajikistan. The sample size for the household survey is 1,200 households. This household sample selection is based mostly on non-probability sampling techniques, and extensively uses the list of households who were beneficiaries of USAID Feed the Future Tajikistan Agriculture and Water Activity (TAWA). The sample is not intended to be representative of the ZOI. The questionnaire contains household-level modules, as well individual-level modules targeted at the main female decision maker in the household. These individual-level modules were to be conducted in private unless infeasible and contain key modules of the Women's Empowerment in Agriculture Index (WEAI).